2009
DOI: 10.20885/jkki.vol7.iss4.art4
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic effect of pinostrobin fingerroot (boesenbergia pandurata)on the culture of hela cells

Abstract: Background: Cancer is one of the leading causes of death worldwide, therefore struggles to find more effective treatment and prevention is needed. Several studies has been performed using natural ingredients, one of which is Temu Kunci (B. pandurata). Temu Kunci extract contains flavonoid pinostrobin that has been showed as having cytotoxicity effects. Cytotoxicity tests of pinostrobin have been performed on several tumor cell lines, but its cytotoxicity effect on HeLa cell line has never been reported. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The IC 50 was determined, as the concentration required to inhibit 50% T47D cell growth and CC 50 was determined, as the concentration required to inhibit 50% Vero cells growth. 9 , 13…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IC 50 was determined, as the concentration required to inhibit 50% T47D cell growth and CC 50 was determined, as the concentration required to inhibit 50% Vero cells growth. 9 , 13…”
Section: Methodsmentioning
confidence: 99%
“…Previously, studies related to pinostrobin showed that its cytotoxic activity against cancer cells was still low compared to anticancer drugs on the market. 2 , 8 , 9 Then supported by the research of Jones & Gehler (2020), pinostrobin selectively decreases the spread of but has less effect on cancer cell death. Although a lot of research has been conducted related to pinostrobin, research related to the modification of its structure is still very rare, especially in the compound pinostrobin propionate and pinostrobin butyrate (Figure 1B,C).…”
Section: Introductionmentioning
confidence: 91%